2021
DOI: 10.3892/etm.2021.9664
|View full text |Cite
|
Sign up to set email alerts
|

Pomelo peel oil alleviates cerebral NLRP3 inflammasome activation in a cardiopulmonary resuscitation rat model

Abstract: The NLR family pyrin domain-containing 3 (NLRP3) inflammasome, which is composed of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC) and pro-caspase-1 protein complexes, is activated by the reactive oxygen species (ROS) that are associated with ischemia-reperfusion (I/R) and are involved in brain damage. Pomelo peel oil (PPO) exhibits antioxidant activity. However, it is unclear whether PPO is able to attenuate NLRP3 inflammasome-induced inflammation and pyroptosis. Healthy male Sprague-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Another group has demonstrated that stroke‐induced white matter damage and microglial pyroptosis can be partially attenuated by suppressing the NF‐κB/NLRP3 signalling pathway 106 . The latest study has indicated that the NF‐κB signalling pathway regulates pyroptosis in microglia post‐CA 107 . Hence, the NF‐κB pathway was strongly connected to cell pyroptosis in nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group has demonstrated that stroke‐induced white matter damage and microglial pyroptosis can be partially attenuated by suppressing the NF‐κB/NLRP3 signalling pathway 106 . The latest study has indicated that the NF‐κB signalling pathway regulates pyroptosis in microglia post‐CA 107 . Hence, the NF‐κB pathway was strongly connected to cell pyroptosis in nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 106 The latest study has indicated that the NF‐κB signalling pathway regulates pyroptosis in microglia post‐CA. 107 Hence, the NF‐κB pathway was strongly connected to cell pyroptosis in nervous system diseases. Consist with studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…We used NDS to identify the protective effect of PPEO and determine the efficacy and safety dose at 50 mg/kg. In fact, different dose of PPEO was adopted due to different research aim in our other studies in the same period [ 6 , 7 ]. Nissl staining and electron microscopy were used to observe the protective effect of PPEO from general to ultrastructural level, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies report that citrus and its products have good antioxidant properties because of its high content of active substances such as terpenes, aldehydes, esters, and ketones [ 5 ]. PPEO, a crude compound extracted from pomelo peel, is considered to have potential therapeutic effects for its antioxidant properties or other biological activities [ 6 , 7 ]. In this study, we selected Shatian pomelo peculiar belonging to Rongxian, Guangxi, and extracted the essential oil from outer peel by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…The observation lead was lead II. The models of CA/CPR in rats were performed as before [ 9 , 22 , 23 ]. In simple terms, CA was induced using an esophageal stimulation electrode (12V) (Chengdu Technology & Market Co., Ltd., Chengdu, China) lasting for 1 min.…”
Section: Methodsmentioning
confidence: 99%